Physical activity ameliorates cardiovascular health in elderly subjects: the functional role of the β adrenergic system - Santulli, Gaetano; Ciccarelli, Michele; Trimarco, Bruno; Iaccarino, Guido (Frontiers in Physiology, 2013)
Aging is a complex process characterized by a gradual decline in organ functional reserves, which eventually reduces the ability to maintain homeostasis. An exquisite feature of elderly subjects, which constitute a growing proportion of the world population, is the high prevalence of cardiovascular disorders, which negatively affect both the quality of life and the life expectancy. It is widely acknowledged that physical activity represents one of the foremost interventions capable in reducing the health burden of cardiovascular disease. Interestingly, the benefits of moderate-intensity physical activity have been established both in young and elderly subjects. Herein we provide a systematic and updated appraisal of the literature exploring the pathophysiological mechanisms evoked by physical activity in the elderly, focusing on the functional role of the β adrenergic system.